2022
DOI: 10.3389/fphar.2022.893634
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of Selected Lamiaceae Essential Oils and Their Monoterpenes Against SARS-Cov-2

Abstract: This study presents the very first report on the in vitro antiviral activity of selected essential oils of Lamiaceae plant species and their monoterpenes against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Nineteen essential oils were obtained by hydrodistillation of dried plant material, and their monoterpene profiles were determined. In addition, the exact concentrations of each monoterpene that were found at a significant level were defined. Both essential oils and their monoterpene compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…Although not clinically tested in COVID-19 patients, this plant has numerous confirmed biological and pharmacological activities (with anti-inflammatory being main one), potentially useful against this disease [ 31 ]. In vitro studies investigating potential of Mentha species against coronavirus demonstrated that essential oil of these species can inhibit the replication of virus in the infected cells [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although not clinically tested in COVID-19 patients, this plant has numerous confirmed biological and pharmacological activities (with anti-inflammatory being main one), potentially useful against this disease [ 31 ]. In vitro studies investigating potential of Mentha species against coronavirus demonstrated that essential oil of these species can inhibit the replication of virus in the infected cells [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…EOs have been proposed as alternative medicines for the treatment of various antiviral diseases [ 12 , 13 ]. Recently, EOs with established pharmacokinetic and pharmacodynamic properties were proposed as an alternative treatment to prevent clinical complications associated with COVID-19 [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fifty micrograms/ml Echinaforce ® (the final concentration of ethanol was 0.2%, and it was proven that the tested coronaviruses were not sensitive to this residual concentration) fully blocked the infectivity of MERS-CoV and SARS-CoV-2. Most recently, one study described the anti-SARS-CoV-2 activity of some Lamiaceae EOs and their monoterpene constituents 58 . The most active essential oil ( Mentha vilosa ) exhibited moderate inhibitory activity (127.00 ± 4.63 ppm), as did carvacrol (80.23 ± 6.07 µM).…”
Section: Resultsmentioning
confidence: 99%